Assessment of knowledge and health care seeking behaviour for menstrual health among adolescent school girls in urban slums of Bengaluru: a cross sectional study - S., Mouna H.; L., Hamsa; T. S., Ranganath; N., Vishwanath (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescent girls are often less informed and less comfortable in accessing reproductive health care and information. Due to taboos and socio-cultural restrictions associated with menstruation and its issues, a culture of silence surrounds it. Every stage of women’s life influences next stage, thus present menstrual health will help the girls to have good reproductive, sexual and maternal health later. Good knowledge and better health care seeking behaviour will help in managing menstruation hygienically and with dignity. Hence the present study was undertaken with the objectives, to assess knowledge about menstruation and to determine health care seeking behaviour for menstrual health among adolescent girls in urban slums. Methods: A cross sectional study was conducted to assess knowledge about menstruation and determine health seeking behaviour for menstrual health among 150 adolescent school girls. Multi stage random sampling with probability proportionate to size sampling technique was used. A pre-tested, semi-structured questionnaire was self administered to assess socio-demographic factors, knowledge and health care seeking behaviour for menstrual health. Results: Among 150 adolescent girls, 102(68.0%) of them had good knowledge. Among girls who had excessive bleeding and irregular menses only half of them sought medical treatment (p<0.05) and though 59.5% had more than one symptoms in a cycle, only 37.3% sought treatment. Conclusions: Health care seeking behaviour for menstrual health among adolescent girls was marginally low, only 34(37.4%) sought treatment.